Fitness Impact of Obligate Intranuclear Bacterial Symbionts Depends on Host Growth Phase - Bella, Chiara; Koehler, Lars; Grosser, Katrin; Berendonk, Thomas U.; Petroni, Giulio; Schrallhammer, Martina (Frontiers in Microbiology, 2016)
Abstract According to text book definition, parasites reduce the fitness of their hosts whereas mutualists provide benefits. But biotic and abiotic factors influence symbiotic interactions, thus under certain circumstances parasites can provide benefits and mutualists can harm their host. Here we addressed the question which intrinsic biotic factors shape a symbiosis and are crucial for the outcome of the interaction between the obligate intranuclear bacterium Holospora caryophila (Alphaproteobacteria; Rickettsiales) and its unicellular eukaryotic host Paramecium biaurelia (Alveolata; Ciliophora). The virulence of H. caryophila, i.e. the negative fitness effect on host division and cell number, was determined by growth assays of several P. biaurelia strains. The performances of genetically identical lines either infected with H. caryophila or symbiont-free were compared. Following factors were considered as potentially influencing the outcome of the interaction: (1) host strain, (2) parasite strain, and (3) growth phases of the host. All three factors revealed a strong effect on the symbiosis. In presence of H. caryophila, the Paramecium density in the stationary growth phase decreased. Conversely, a positive effect of the bacteria during the exponential phase was observed for several host × parasite combinations resulting in an increased growth rate of infected P. biaurelia. Furthermore, the fitness impact of the tested endosymbionts on different P. biaurelia lines was not only dependent on one of the two involved strains but distinct for the specific combination. Depending on the current host growth phase, the presence of H. caryophila can be harmful or advantageous for P. biaurelia. Thus, under the tested experimental conditions, the symbionts can switch from the provision of benefits to the exploitation of host resources within the same host population and a time-span of less than six days.